2015
DOI: 10.1186/s12882-015-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding barriers to optimal medication management for those requiring long-term dialysis: rationale and design for an observational study, and a quantitative description of study variables and data

Abstract: BackgroundRates of medication non-adherence in dialysis patients are high, and improving adherence is likely to improve outcomes. Few data are available regarding factors associated with medication adherence in dialysis patients, and these data are needed to inform effective intervention strategies.Methods/designThis is an observational cross-sectional study of a multi-ethnic dialysis cohort from New Zealand, with the main data collection tool being an interviewer-assisted survey. A total of 100 participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…Our results were in accordance with the possible reasons for nonadherence such as forgetting medication and frequent dosing in previous studies (27). This can be improved through patient training, mainly highlighting the importance of adherence.…”
Section: Discussionsupporting
confidence: 80%
“…Our results were in accordance with the possible reasons for nonadherence such as forgetting medication and frequent dosing in previous studies (27). This can be improved through patient training, mainly highlighting the importance of adherence.…”
Section: Discussionsupporting
confidence: 80%
“…It has been widely used in adherence research for multiple disease states and medications across numerous countries. [14][15][16][17] In this study, the MMAS-8 was used to assess for self-reported low adherence in general and was not grounded in any specific conditions or medications. MMAS-8 scores can range from 0 to 8 with low adherence defined as a score <6, medium adherence as scores of 6 or 7 and high adherence with a score of 8.…”
Section: Medication Adherencementioning
confidence: 99%
“…The indicator inappropriate use of medicines was also specific to infer ND under the analysis, and the absence of this indicator indicates the absence of this diagnosis. This indicator occurs because of difficulty in access to medicines, poor understanding, and forgetfulness (Aspden et al, 2015). Therefore, there is a need for professional support for these patients to minimize the difficulties of the prescribed pharmacological treatment.…”
Section: Discussionmentioning
confidence: 99%